Anti-Corruption Character Education in Children of Early Age - Drajat, , Manpan (International Journal of Psychosocial Rehabilitation, 2020)
Corruption is an extraordinary crime that requires comprehensive handling. It is not enough just to enforce the law, but also must be another approach so that Indonesia could be free from corruption. One of the ways is through education. Education can produce new generation that effectively replaces the older generation which tends to be corrupt. Education, more specifically, anti-corruption character education is best planted from an early age. This study aims to analyze character education in early childhood who are able to build anti-corruption character from an early age. This research is a phenomenological quality research involving two early childhood educational institutions that are concerned in building children's character. These two institutions have been effective in building anti-corruption characters such as honesty, responsibility, etc. These institutions are PAUD Bukit Pelangi, Jatinangor Sumedang and RA Salsabila Purwakarta. The data of this study are collected by observation, interview, documentation and FGD (Focus Group Discussion). Data were analyzed using interactive analysis techniques. The research discoveries show that the two schools are quite effective in building children's character education especially honesty and responsibility as the main capital of anti-corruption attitude. The two schools use the BCCT translation center method developed by Pamela from Florida.